Archaeology after the End of history - Plantzos, Dimitris (Historein, 2013)
This paper offers a survey of the rapid changes observed in the field of archaeological theory in the last 20 years or so; in the midst of cataclysmic changes in the way scholars, and the public at large, attempt to comprehend the past, archaeologists have learnt to trust significantly less their valuable raw data and "facts", in favour of more nuanced accounts allowing for the complexity of the phenomena they study. More to the point, they slowly realise that, as historians, they are internal to the problems under their scrutiny.